Complex diagnostics of ordinary chondrites Markovka, Polujamki, Sayh al Uhaymir 001, Dhofar 020, and Jiddat al Harasis 055 by X‐ray techniques and Mössbauer spectroscopy. (20th December 2021) - Guda, Liubov V.; Kravtsova, Antonina N.; Kubrin, Stanislav P.; Guda, Alexander A.; Mazuritskiy, Mikhail I.; Tereshchenko, Andrei A.; Popov, Yuri V.; Soldatov, Alexander V.
Abstract: Micro X‐ray fluorescence (XRF) analysis, scanning electron microscopy (SEM), energy‐dispersive X‐ray spectroscopy (EDX), X‐ray diffraction (XRD), and Mössbauer and X‐ray absorption near‐edge structure (XANES) spectroscopies have been used to study the element and phase composition, and Fe and Ni oxidation states in ordinary chondrites. The meteorites have been initially classified as Markovka (H4 type), Polujamki (H4 type), Sayh al Uhaymir (SaU) 001 (L5 type), Dhofar (Dho) 020 (H4/5 type), and Jiddat al Harasis (JaH) 055 (L4‐5 type). We have applied a set of spectroscopic methods to characterize and quantify the differences between samples. While the concentration of Fe in the meteorites is in agreement with the qualitative assignment of their types (L or H) made upon discovery, we observed extremely low Mg/Si and Al/Si values compared to the data published by Palme et al. (2014). Phase content of the meteorites has been studied by means of XRD, as well as by SEM and EDX. Mössbauer spectroscopy of Fe‐containing phases has determined that Fe ions are present mainly in olivine and pyroxene phases in all studied samples. Goethite, hematite, and troilite phases were found in Markovka, Polujamki, and Sayh al Uhaymir 001, respectively. Markovka and Polujamki samples contained the largest concentration of Fe‐Ni‐Co metal grains. Fe and Ni K ‐XANES spectra were analyzed to estimate metal oxidation state in the chondrites and compared with the Mössbauer data. The multispectral data acquired in the present work are of importance for further understanding of meteoritic processes.